The effect of political products on the decision to choose political party through the role of the candidates of legislative members as mediating variable - Suwignyo Widagdo (Universitas Hayam Wuruk Perbanas, 2015)
This study attempts to analyze; 1) the effect of political product on the decision to choose the candidate of legislative member; 2) the effect of political product on the decision to choose political party; 3) the effect of the decision to choose the candidates of legislative members on the decision to choose political party; and 4) the role of mediating variable of the decision to choose the candidate of legislative member on the affect the decision to choose political party. The data were analyzed using inferential statistical analysis of Generalized Structured Component Analysis (GeSCA). It shows that 1) the political product has an effect on the decision to choose the candidate of legislative member; 2) the mediating variable of the decision to choose the candidate of legislative member plays a very important role for the constituents in taking the decision to choose political party. However, of the existing three indicators, only personal characteristic can explain the strength of the effect of political product on the selection of political party. Yet, the second hypothesis test result shows that the path coefficient is significant and provides evidence that the second hypothesis is accepted. The decision to choose political party is increa-singly stronger as a result of the decision to choose the candidate of legislative member which is in accordance with the expectations of voters. Acquisition of the party vote will increase after the constituents know the candidates proposed. The higher the popularity and quality of the candidate is, the greater the electoral gains of a party.